2019
DOI: 10.1177/109258721902400103
|View full text |Cite
|
Sign up to set email alerts
|

The Place of Inspiration in Heritage Interpretation: A Conceptual Analysis

Abstract: Inspiration has been an under-studied phenomenon in the interpretation field. This paper presents the results of a systematic literature review of psychological literature related to inspiration, revealing nine characteristics of inspiration. Of particular interest was the contrasting meanings of inspiration as inspired by and inspired to, and that inspiration is transmissible, positive, individual, transcendent, unexpected, and holistic, and requires receptivity, which may be cultivated. Each characteristic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…The results of this effort appear in a series of four articles published as a special issue in the Journal (2013-18(2)). Their study provided empirical Barrett et al (2017), Beck et al (2015), Benton andSinha (2011), Bixler et al (2015), Bourque et al (2014), Britt (2017), Burris (2019), Douglas et al (2018), Gilson and Kool (2019), Hall et al (2010), Ham (2013), Henker and Brown (2011), Knapp and Forist (2014), Lawhon et al (2017), Macklin et al (2010), Montero et al (2018), Morgan and Hwang (2014), Moss et al (2010), Ogle (2016), Stern (2013a, 2013b), Price et al (2018), Rahaman and Kian (2017), Reese (2013), Ren and Folta (2016),…”
Section: Interpretive Techniquesmentioning
confidence: 99%
“…The results of this effort appear in a series of four articles published as a special issue in the Journal (2013-18(2)). Their study provided empirical Barrett et al (2017), Beck et al (2015), Benton andSinha (2011), Bixler et al (2015), Bourque et al (2014), Britt (2017), Burris (2019), Douglas et al (2018), Gilson and Kool (2019), Hall et al (2010), Ham (2013), Henker and Brown (2011), Knapp and Forist (2014), Lawhon et al (2017), Macklin et al (2010), Montero et al (2018), Morgan and Hwang (2014), Moss et al (2010), Ogle (2016), Stern (2013a, 2013b), Price et al (2018), Rahaman and Kian (2017), Reese (2013), Ren and Folta (2016),…”
Section: Interpretive Techniquesmentioning
confidence: 99%
“…Indeed, inspiration can be nurtured (Gilson, 2015)—we can work to ‘woo or invite it’ (Hart, 1998: 26 quoted in Gilson, 2015: 59; also Latham et al, 2018). A substantial body of literature outlines precisely how and why we might seek to generate such emotive engagement in the cultural heritage sector.…”
Section: How Do We Generate Enchantment?mentioning
confidence: 99%
“…People generally want to explore ‘complex, controversial topics’ in museum contexts (Carnall et al, 2013: 66); and major research endeavours across multiple continents demonstrate that people do not expect cultural institutions to be neutral but rather to ‘have a social responsibility to take a leading role in inspiring people's social and political activism in order to help bring about change’ (Lynch, 2017: 24). As suggested above, we can prime people to be open to these points of inspiration (Gilson, 2015) and craft meaningful experiences for people even if they do not match typical preferences (see Pekarik et al, 2014). Moreover, the literature shows that professionals regularly wrongly judge their audiences, underestimating their ‘capacity… to respond and debate—to be challenged’ (Lynch, 2013: 6).…”
Section: Changing the World Through Archaeology And Heritagementioning
confidence: 99%
“…This study focused solely on the concept of inspiration; while we recognize that there are other psychological responses to the work of interpreters including experiences like novelty and awe, we did not investigate anything but inspiration. Our paper begins with a brief summary of the nine aspects of inspiration offered in Gilson & Kool (2019). We then present the online World Café methods used to elicit interpreters’ thoughts about inspiration and its place in interpretation, and end with our analysis of the café-generated data.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper (Gilson & Kool, 2019) we offered a conceptual analysis of inspiration as it might apply in the context of heritage interpretation. Carrying out a review of the psychological literature on inspiration available at the time (≈30 papers) and then integrating it with the work of interpreters through Gilson's doctoral research, we identified nine aspects of inspiration that might be relevant to interpretation as a field of practice.…”
Section: Introductionmentioning
confidence: 99%